SecDCP: Secure dynamic cache partitioning for efficient timing channel protection - Yao Wang; Ferraiuolo, Andrew; Danfeng Zhang; Myers, Andrew C.; Suh, G. Edward (2016 53nd ACM/EDAC/IEEE Design Automation Conference (DAC), 2016)
In today's multicore processors, the last-level cache is often shared by multiple concurrently running processes to make efficient use of hardware resources. However, previous studies have shown that a shared cache is vulnerable to timing channel attacks that leak confidential information from one process to another. Static cache partitioning can eliminate the cache timing channels but incurs significant performance overhead. In this paper, we propose Secure Dynamic Cache Partitioning (SecDCP), a partitioning technique that defeats cache timing channel attacks. The SecDCP scheme changes the size of cache partitions at run time for better performance while preventing insecure information leakage between processes. For cache-sensitive multiprogram workloads, our experimental results show that SecDCP improves performance by up to 43% and by an average of 12.5% over static cache partitioning.